THE EFFECT OF PROFITABILITY AND SOLVABILITY ON COMPANY VALUE AT PT. GUDANG GARAM Tbk (2018-2023 PERIOD) - Hikmatul Aliyah; Septiana M.S; Nadila Apriyanti; Siti Nur’ Aida (Majapahit Journal of Islamic Finance and Management, 2026)
The increasingly competitive cosmetics industry pushes Wardah to implement effective marketing strategies and reach ideal sales targets. Pemasaran strategies and achievement metrics are crucial in influencing consumer purchasing decisions. Because of this, the purpose of this study is to analyze the impact of these two factors on the decision to purchase Wardah products at Toko Femina Metro Lampung. The purpose of this study is to analyze the impact of pemasaran strategies and achievement metrics on consumer demand for Wardah products. In addition, this study aims to understand the simultaneous effects of the two variables in question at Toko Femina Metro Lampung. This study uses a quantitative approach with an asosiatif approach. The research sample consists of Wardah product consumers at Toko Femina Metro Lampung who are selected using the purposive sampling technique. Data analysis techniques that are used include validity and reliability tests, regression analysis of the berganda line, t and F tests, and coefficient of determination (R2). The study's findings indicate that pemasaran strategies and achievement levels have a positive and significant impact on consumers' willingness to purchase Wardah products. In a parallel or simultaneous manner, these two variables increase purchasing power, with the pemasaran strategy being the most dominant factor. This study's implications indicate that increasing the effectiveness of pemasaran strategies and consistent target penjualan can significantly increase consumer purchasing decisions.